Correction to "Wide-Area Backup Protection Algorithm Based on Fault Component Voltage Distribution" [Oct 11 2752-2760] - He, Zhiqin; Zhang, Zhe; Chen, Wei; Malik, Om P.; Yin, Xianggen (IEEE transactions on power delivery, 2012)
In the above titled paper (ibid., vol. 26, no. 4, pp. 2752-2760, Oct. 2011), Figs. 1 and 2 appear incorrectly. The correct figures are presented here.